Digital mapping of micronutrients in soils of Ramban district of J&K using Geographic Information System - WANI, OWAIS ALI; SHARMA, K.R.; SHARMA, VIKAS; KUMAR, SHAMAL S.; MAHDI, SYED SHERAZ; BANGROO, SHABIR A.; MALIK, A. RAOUF (Journal of Soil and Water Conservation, 2024)
Maps of soil nutrients are based on intensive soil sampling which are helpful in implementing sitespecific management strategies. At various sampling scales, geostatistical methods have been widely employed to determine the spatial correlation and range of spatial dependency. The objective of this paper was to assess the DTPA extractable micronutrients of Ramban district soils and generate their prediction maps. The process of digitization and generation of maps was carried out with ArcGIS 10.0 software following Inverse distance weight (IDW). The DTPA-Zn content of soils of Ramban varied widely as low as 0.11 mg Zn kg-1 and as high as 1.61 mg Zn kg-1 with a mean value of 0.78 mg Zn kg-1. DTPA-ranged from 0.11 mg Cu kg-1 to 1.82 mg Cu kg-1 with a mean value of 0.85 mg Cu kg-1. DTPA-Fe ranged from 6.30 mg Fe kg-1 to 34.50 mg Fe kg-1 with a mean value of 19.17 mg Fe kg-1. DTPA-Mn ranged from 2.40 mg Mn kg-1 to 31.50 mg Mn kg-1 with a mean value of 18.24 mg Mn kg-1. Available boron (B) ranged from 0.11 ppm to 3.60 ppm with a mean value of 1.05 ppm. Cu, Zn, and B were the most deficient micronutrients evaluated; a regular supply of organic matter and pH adjustment is recommended. Micronutrient deficiency and erosion are important obstacles in the district’s agriculture. Farmers and researchers will be able to use the spatial maps on micronutrient status created during the investigation to address nutrient deficiency in specific locations and to guide farmers in determining the amount and type of nutrient to apply for maximum returns.